Inequality of access in irrigation systems of the mid-hills of Nepal - Pariyar, Bishnu; Lovett, Jon C.; Snell, Carolyn (Area development and policy, 2018)
Access to, and control over, water for irrigation is one of the most important factors for increasing agricultural productivity, thereby affecting household food security and levels of poverty in developing countries. However, investments in the irrigation sector have often failed to consider equity aspects of irrigation interventions. Using data from 199 households from three irrigation systems in the mid-hills of Nepal, we analyse access and control of water in different levels of socio-economic heterogeneities. The results demonstrate that efforts to improve livelihoods of the rural poor should give due consideration to the distributional aspects of irrigation interventions, with authority for allocating the level of access to irrigation water given to the farmers throughout the system.